Associations between COVID-19 pandemic impact, dimensions of behavior and eating disorders: a longitudinal UK-based study - K. Ioannidis (European Psychiatry, 2022)
Introduction There is growing concern about how people with eating disorders are impacted by the widespread societal restructuring during the COVID-19 crisis.